Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1177/0142331219894811
|View full text |Cite
|
Sign up to set email alerts
|

An investigation to the design of high-precision wind sensing device based on piezoelectric array

Abstract: A new wind sensing device based on bimorphs array is designed for apperceiving wind direction and velocity, whose structure is an L-shaped cantilevers array. A coupling model of the array is proposed to predict the response voltage stimulated by wind. By extracting the response voltage ([Formula: see text]) on each bimorph cantilever, the values of wind direction ([Formula: see text]) and velocity ([Formula: see text]) can be calculated in terms of the geometric relation. Further, the relations among wind erro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Based on the basic situation, this article mainly calculates and analyses the company's debt-to-asset ratio, return on net assets, net sales interest rate, and total asset turnover rate. According to the various values in Table 4, it can be concluded that the financial indicators of the enterprise in the year (2015) have been significantly improved when the business of a business changed the investment in real estate measurement model (2015) [14]. However, the improvement of financial indicators in the following years is relatively small.…”
Section: Impact On Financial Indicatorsmentioning
confidence: 99%
“…Based on the basic situation, this article mainly calculates and analyses the company's debt-to-asset ratio, return on net assets, net sales interest rate, and total asset turnover rate. According to the various values in Table 4, it can be concluded that the financial indicators of the enterprise in the year (2015) have been significantly improved when the business of a business changed the investment in real estate measurement model (2015) [14]. However, the improvement of financial indicators in the following years is relatively small.…”
Section: Impact On Financial Indicatorsmentioning
confidence: 99%
“…After measuring the local deformation of the substrate surface, the sensor further calculates the bending deformation of the cantilever and then infers the type, direction, position and frequency of the external pressure [13,14]. Several types of sensors have been used, including resistance [15], Hall effect magnetic [16][17][18], capacitor microphone [19,20], and piezoelectric bimorph [21,22] sensors. This particular type of artificial whisker has a simple structure, can be designed and manufactured using existing semiconductor technology, and has been deeply researched and extensively applied.…”
Section: Introductionmentioning
confidence: 99%